Awareness regarding body and organ donation amongst the population of an urban city in India - Bharambe, Vaishaly K.; H., Rathod; M., Paranjape V.; N., Kanaskar; S., Shevade; K., Survase; V., Arole; Sakshi, Singh; Gaurav, Brahmbhatt; Feroz, Alam (Journal of Health and Allied Sciences NU, 2015)
Purpose : Bodies for purpose of dissection and organs for transplantation surgeries are needed for education of medical students and treatment of cases of end-stage organ failure. However deceased organ donation rate in India is very dismal. In the present study the authors assess the knowledge and attitude of the people living in an urban city in India towards organ and body donation.Materials/Methods : A questionnaire was distributed amongst all willing patients and their relatives attending the out-patient Department at our Hospital. This was followed by an awareness session wherein the researchers discussed body and organ donation and its need in India. Information sheet was handed to all and the willing respondents were given eye and body donation forms, and donor cards.Result: 41/65 people consented to participate. 41.5%, 31.7%, 12.2% and 12.2% had obtained knowledge regarding organ donation from newspaper, television, family members and internet respectively. 26.8% claimed that they were imparted knowledge by health care professionals. 78%, 53.7% and 19.5% were aware about eye, kidney and liver donations respectively. 17.1% were aware of body and lung donation each. Awareness of donation of other organs was found to be in the range between 4.9% to 14.6%. 43.9% were willing to be organ donors and 3 persons filled the body donation forms.Conclusion: Newspapers, healthcare professionals could be utilized to further the awareness regarding body and organ donation. Carrying out awareness programmes will help to reach information to each individual, clarifying any myths and increasing understanding and motivation levels among
Keywords: Organ donation; body donation; awareness; donor card; donation forms